Analisis Ketahanan Pangan pada Rumah Tangga di Desa Miskin di Kecamatan Sumbang Kabupaten Banyumas - Neni Widayaningsih; Barokatuminalloh Barokatuminalloh (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2011)
The purpose of this research is to analyze the level of household food security, in the village with the most number of poor households, to know the income level of households with food insecure households criteria; and know the benefits of government programs such as Raskin (rice for poor people) for household food security in sub donates Banyumas. Total population in this research are 8333 families who belong to the target households (RTS) Raskin, while samples that were studied were 100 respondents with multiple stages sampling method. The method of analysis in this research uses a qualitative analysis, the method Current Population Survey (CPS) Food Security Suplement, and tabulation method. The results of this research, respondents indicated that most households (RTS) in the district donates Raskin was on the status of food insecurity without hunger, both in group household had children under the age of 18 years (71 percents), and households that are not have children under the age of 18 years (66 percents). Food insecurity status of the majority (73.8 percents,) are in the category of poor households based on criteria of BPS. Keywords: Food Security, Income Limit Hold Food, Food Rawan, Social Protection Programme, Target Households Raskin